Risk assessment via genotoxicity, metabolism, apoptosis, and cell growth effects in a HepG2/C3A cell line upon treatment with Rubus rosifolius (Rosaceae) leaves extract - Quadros, Ana Paula Oliveira De [UNESP]; Almeida, Laíza Moura [UNESP]; Petreanu, Marcel; Niero, Rivaldo; Rosa, Paulo Cesar Pires; Sawaya, Alexandra Christinie Helena Frankland; Mantovani, Mario Sergio; Gaivão, Isabel O’Neill De Mascarenhas; Maistro, Edson Luis [UNESP] (Taylor & Francis, 2020)
Rubus rosifolius: Sm. (Rosaceae) is a plant traditionally used in Brazil and some other countries to treat diarrhea, stomach diseases, and as an analgesic, antimicrobial, antihypertensive, and as well as other pharmacological properties. The aim of this study was to examine cytotoxic and genotoxic effects of R. rosifolius leaves extract on HepG2/C3A cells and correlate these findings with the expression of mRNA to underlying mechanisms of action. At concentrations between 0.01 and 100 µg/ml, cytotoxic effects were not detected by the MTT assay. This was confirmed by mRNA induction of the CYP3A4 gene (by RT-qPCR assay). However, genotoxic effects occurred at treatments from 1 µg/ml extract (comet and micronucleus test). An increase in the number of cells in S phase was observed at 100 µg/ml, and an elevation in apoptotic cell number was found for all tested concentrations (10, 20, or 100 µg/ml) (cell cycle and apoptosis analysis by flow cytometry). The genotoxicity induced by the extract was the main cause of the rise in the number of cells undergoing apoptosis, as indicated by rise in mRNA of CASP7 gene, and elevation of cells in the S phase of the cell cycle at the higher tested concentrations, as an attempt to repair genetic damage that occurred. These observations suggest that, despite its pharmacological potential, the use of R. rosifolius leaves extract may pose a risk to the integrity of the genetic material of human cells.
Keywords: apoptosis; Cell cycle; comet assay; cytotoxicity; gene expression; genotoxicity; rosaceae toxicity